2014
DOI: 10.3389/fnagi.2014.00078
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biomarker Changes in Premanifest Huntington Disease Show Trial Feasibility: A Decade of the PREDICT-HD Study

Abstract: There is growing consensus that intervention and treatment of Huntington disease (HD) should occur at the earliest stage possible. Various early-intervention methods for this fatal neurodegenerative disease have been identified, but preventive clinical trials for HD are limited by a lack of knowledge of the natural history of the disease and a dearth of appropriate outcome measures. Objectives of the current study are to document the natural history of premanifest HD progression in the largest cohort ever stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
228
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(251 citation statements)
references
References 32 publications
18
228
0
1
Order By: Relevance
“…Decades of research have long established that cognitive function declines in the premanifest and early stages of HD (62)(63)(64). Although several studies point to the contribution of other brain structures such as the hippocampus to learning and memory defiwith our hypothesis, KI mutant mice showed a significant increase in hippocampal RhoA activity compared with either WT, p75 +/-, or KI:p75 +/-mice ( Figure 10A).…”
Section: Discussionmentioning
confidence: 57%
“…Decades of research have long established that cognitive function declines in the premanifest and early stages of HD (62)(63)(64). Although several studies point to the contribution of other brain structures such as the hippocampus to learning and memory defiwith our hypothesis, KI mutant mice showed a significant increase in hippocampal RhoA activity compared with either WT, p75 +/-, or KI:p75 +/-mice ( Figure 10A).…”
Section: Discussionmentioning
confidence: 57%
“…This is also supported by an HD animal model study that showed an inverse relationship between striatal volume and cortical thickness, indicating that thickening may be compensatory (Lerch et al, 2008). The volume of the caudate and putamen has been shown to be the most powerful biomarker for prediction of motor signs of the disease (Paulsen et al, 2014). Although the cerebellum is not commonly reported as being structurally abnormal in pre-HD subjects, a recent report documented abnormal cortico-cerebellar connectivity in patients with early-manifest HD (Wolf et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of these diverse developmental defects for HD pathogenesis remains undefined, they have the potential to impair the integrity of striatal and cortical neuronal homeostasis and function through multiple inductive interactions. Indeed, these changes may provide an explanation for studies, including the Neurobiological Predictors of Huntington's Disease (PREDICT-HD) and TRACK-HD studies, showing electrophysiological abnormalities, discrete brain structural as well as volumetric changes, and cognitive and motor deficits occurring long before disease onset (3)(4)(5)(6)(7)(8). We therefore propose that selective exposure to mutant Htt (mHtt) during neural development can recapitulate characteristic features of HD.…”
mentioning
confidence: 99%